(untitled) (Dissertare, 2020)
The Deaf Culture was invisible in America from modernity, because, as a result of the homogeneous vision that the West had of the new continent, this culture was placed outside space-time. Faced with this reality, the need to build rationality emerged from the differentiated stories and from the socio-historical reality itself. In view of this logic, this work focuses on reviewing the evolution of visions on deafness, the conceptual aspects related to the Deaf Culture, as well as its challenges in the Venezuelan context, from the socio-anthropological approach of the deafness, with special reference to the Venezuelan Sign Language (VSL), as a cohesive element of the Deaf Culture in the country. The work, of a theoretical-descriptive nature, is based on the literature review As a final consideration, it is highlighted that from the socio-anthropological approach, the Deaf population organized and used strategies to cultivate their identity and keep their language alive, Venezuelan Sign Language (VSL),